2019
DOI: 10.4317/jced.56002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of restorative material and ceramic thickness on CAD\CAM endocrowns

Abstract: The impact of restorative material and ceramic thickness on CAD\CAM endocrowns e969

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
1
20
0
3
Order By: Relevance
“…However, the oblique incidence of chewing loads and cusp heights [ 9 ] also can affect the endocrown mechanical behavior and different occlusal anatomy can promote different results. However, for the molar region, the high incidence of axial loads in the posterior region makes the endocrown treatment a reliable modality considering the restoration fracture [ 12 , 14 ]. This study was also in agreement with this reported behavior, since the stress concentrations in the restoration cross-section and intaglio surface are not very different between the groups ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the oblique incidence of chewing loads and cusp heights [ 9 ] also can affect the endocrown mechanical behavior and different occlusal anatomy can promote different results. However, for the molar region, the high incidence of axial loads in the posterior region makes the endocrown treatment a reliable modality considering the restoration fracture [ 12 , 14 ]. This study was also in agreement with this reported behavior, since the stress concentrations in the restoration cross-section and intaglio surface are not very different between the groups ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out investigating the restorative material used to perform the endocrown treatment, reporting the use of ceramics, nanocomposites, and hybrid materials [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In addition, clinical cases reported the use of acrylic resin [ 15 ], resin composite [ 16 ], and bis-acrylic resin [ 17 ] as restorative material for the manufacturing of interim endocrowns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although maximum masticatory forces in mouth range between 597 N (women) and 847 N (men), in the molar region these forces can reach up to 900 N (Waltimo & Könönen, 1993). According to the literature, there are studies that have found the fracture strength of endocrowns to be much higher (Aktas et al, 2018; Gresnigt et al, 2016; Tribst et al, 2019). The fracture strength values in the present study are relatively lower than those in previous studies and this finding could be attributed to the differences in cavity preparation design, axis and point of applied force.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this is regarded as a potential threat, knowing that remaining coronal tooth structure fractured. Lithium disilicate ceramic materials presented acceptable survival and fracture load as long as the material's minimum thickness and the enamel adhesion are respected [32]. In the 4 mm endocrown, the cement layer is far away from the load point, which is a protection.…”
Section: Discussionmentioning
confidence: 99%